3CA-FO: Budget stereoscopic 3D imaging colposcope - Nontiwat Amnuayphol; Wibool Piyawattanametha; Nicholas Piyawattanametha (My University, 2023)
This research aims to develop an advanced medical device designed to enhance the diagnostic quality of conventional colposcopy. The device utilizes cutting-edge technologies, including 3D image synthesis via stereoscopic imaging and polarized glasses as the primary focus of the study is to improve cervical cancer. The research scope encompasses enhancing spatial information, The research scope involves enhancing spatial information while allowing the doctor to maintain the advantage of near vision and enabling multi-angle imaging. The hardware of the colposcope is based on the design from Duke University's 2018 research. Our 3D Cervical Assessment - Fine-tuned Optics colposcope (3CA-FO) is capable of providing real-time 3D imaging with precise calibration, achieved through the utilization of the Embedded Mono Calibration for Heterogeneous Lenses technique. This ensures an instantaneous and high-quality 3D output response.
Keywords: Cervical Cancer and HPV Research; Female Genital Mutilation/Cutting Issues